PENGARUH SHOPPING LIFE STYLE, FASHION INVOLVEMENT, HEDONIC SHOPPING MOTIVATION DAN SALES PROMOTION TERHADAP IMPULSE BUYING DI MALANG TOWN SQUARE, DAN MALL OLYMPIC GARDEN (Study pada Mahasiswa Fakultas Ekonomi Universitas Islam Malang) - Ummi Mardhotus Sholihah; N. Rachma; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study aims to determine the effect of Shopping Lifestyle, Fashion Involvement, Hedoconic Shopping Motivation, and Sales Promotion to Impulse Buying in Malang Twon Square, Olympic Garden Mall, study on the students of Faculty of Economics of Islamic University of Malang. To be able to achieve the goal used method of analysis of data of normality test, multiple linear regression, classical assumption test, F-test & t test. Data collection methods in this study using questionnaires distributed to students of the Faculty of Economics, Islamic University of Malang.Population in this research is student of Faculty of Economics from class of 2013/2014 until 2016/2017. The use of samples using nonprobability sampling technique using the method of accidental sampling with the criteria obtained 96 respondents who became the sample in this study.Based on the results of analysis and discussion, it can be concluded that simultaneously Shopping Lifestyle, Fashion Involvement, Hedoconic Shopping Motivation, and Sales Promotion significantly influence Impulse Buying. While partially Shopping Lifestyle, Fashion Involvement, Hedonic Shopping Motivation, Sales Promotion significantly influence Impulse Buying in Malang Twon Square, Olympic Garden Mall, study on students of Faculty of Economics, Islamic University of Malang .Keywords: Shopping Lifestyle, Fashion Involvement, Hedonic Shopping Motivation, and Sales Promotion, Impulse Buying.